2020
DOI: 10.21203/rs.3.rs-18957/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of PVT1 Polymorphisms in the Glioma Susceptibility and Prognosis

Abstract: Background: Genetic factors play a crucial role in the glioma risk and prognosis of glioma patients. To explore the role of PVT1 polymorphism in the susceptibility and survival of glioma in the Chinese Han population, we conducted a case-control study.Methods: The three single-nucleotide polymorphisms (SNPs) in PVT1 were genotyped using Agena MassARRAY from 575 patients with glioma and 500 healthy controls. We used the χ 2 test to analyze the differences in distribution of allele and genotype between the cases… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The T allele of rs13255292 has also been shown to reduce the risk of ovarian cancer in women taking oral contraceptive pill [32] . Further, the recessive model (TT) of rs13255292 has been shown to decrease the risk of glioma in the male [33] . A previous study investigated the association between the genetic polymorphisms of PVT1 and the risk of lung cancer [34] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The T allele of rs13255292 has also been shown to reduce the risk of ovarian cancer in women taking oral contraceptive pill [32] . Further, the recessive model (TT) of rs13255292 has been shown to decrease the risk of glioma in the male [33] . A previous study investigated the association between the genetic polymorphisms of PVT1 and the risk of lung cancer [34] .…”
Section: Discussionmentioning
confidence: 99%
“…[32] Further, the recessive model (TT) of rs13255292 has been shown to decrease the risk of glioma in the male. [33] A previous study investigated the association between the genetic polymorphisms of PVT1 and the risk of lung cancer. [34] However, no statistically significant relationship was found between rs2608053 polymorphisms in PVT1 and the risk of lung cancer in the overall population.…”
Section: Discussionmentioning
confidence: 99%
“…Ding et al. reported that while rs13255292 and rs4410871 increased susceptibility to glioma in the Chinese Han population, they do not have a prognostic value ( 129 ).…”
Section: Lncrnas In Gliomamentioning
confidence: 99%
“…While the pathogenesis remains unclear, high-dose ionizing radiation exposure is believed to be a major risk factor. Previous studies have mostly used multivariate logistic regression models or Cox proportional hazard models to analyze factors related to end-point events (7,8). These models have high requirements on the sample size and related parameters of the study, which greatly limits the development of clinical research.…”
Section: Introductionmentioning
confidence: 99%